Pengembangan Lembar Kerja Mahasiswa (LKM) Berbasis Eksplorasi Jamur Makroskopis - Yuni Krisnawati; Linna Fitriani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to produce student worksheets based on macroscopic mushroom exploration in the Low Plant Taxonomy (TTR) course at STKIP-PGRI Lubuklinggau. South Sumatra that is feasible and effective. This research is a development study using the 4D development model from Thiagarajan. Research data in the form of macroscopic fungi, validation results from validators, student questionnaire responses, and tests were analyzed descriptively and quantitatively. Based on exploration results, the macroscopic mushroom species identified were 24 species from 16 families, 7 genera, 2 classes and 2 divisions. The results of the analysis showed that the MFI developed was feasible (very valid), received positive responses from students with strong criteria, and the percentage of mastery learning was 92.3% with very high learning effectiveness criteria, Conclusions, Student Worksheets (LKM) developed were valid and feasible for student use, and has significantly high effectiveness in student learning in the Low Plant Taxonomy (TTR) course at STKIP-PGRI Lubuklinggau. Keywords: Macroscopic Mushroom, Student Worksheet, Design Model of 4D Thiagarajan